A study of customers satisfaction towards Avon’s cosmetic product / Asmawati Sajari - Sajari, Asmawati (2011)
Customer satisfaction means the degree of overall pleasure felt by the customers, resulting from the ability of the product or services to fulfill the customer’s desires expectations. The objective of this study is to investigate factors that influence the customer satisfaction towards Avon cosmetics products. The factors are the independent variables such price, product quality and service quality. The primary data analyze in this study gathered from questionnaires distributed to the Avon customers at three Avon outlets in Seberang Perai Tengah. By using the convenience sampling method, there are 120 respondents who answered the questionnaires. The data were analyzed by using Statistical Package for Social Science (SPSS) to get the accurate statistical results. The result of this study shows that the independent variables have relationship with dependent variable. The finding of this research shows that there is a relationship between those variables. As a whole, the two independent variables were found to be significantly related to customer satisfaction.